2019
DOI: 10.1093/jac/dkz483
|View full text |Cite
|
Sign up to set email alerts
|

Do vegetarians less frequently carry ESBL/pAmpC-producing Escherichia coli/Klebsiella pneumoniae compared with non-vegetarians?

Abstract: Background ESBL and plasmid-mediated AmpC (pAmpC)-producing Enterobacteriaceae are frequently found on meat products in Dutch retail, especially on poultry. Objectives We investigated whether vegetarians are at lower risk of carrying ESBL/pAmpC-producing Escherichia coli/Klebsiella pneumoniae (ESBL-E/K) compared with persons who consume meat. Methods Vegetari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Another study reported higher levels of excretion of ESBL between July and September, although this was inversely correlated with use of antimicrobials (55). However, some factors that could explain this variation in prevalence, such as outdoor activity, different feed preparation methods, and increased movement, are not applicable for dairies in Québec (56). Nevertheless, even if animals did not have access to the outside for the majority of farms, buildings were often opened to allow better aeration during the summer.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported higher levels of excretion of ESBL between July and September, although this was inversely correlated with use of antimicrobials (55). However, some factors that could explain this variation in prevalence, such as outdoor activity, different feed preparation methods, and increased movement, are not applicable for dairies in Québec (56). Nevertheless, even if animals did not have access to the outside for the majority of farms, buildings were often opened to allow better aeration during the summer.…”
Section: Discussionmentioning
confidence: 99%
“…Though the proportion of infections caused by MDR ST131 E. coli is lower in the community than in the hospital sector the fecal carriage of the pathogen is not rare in outpatients and the general population and can last for extensive time periods (Gurnee et al, 2015;Nakane et al, 2016;Ny et al, 2017;Huang et al, 2018;Morales Barroso et al, 2018;Teunis et al, 2018;Birgy et al, 2019;Meijs et al, 2019). The question arises how can MDR ST131 E. coli strains persist in the intestinal flora in the community without ostensible antibiotic exposure?…”
Section: Multidrug-resistant E Colimentioning
confidence: 99%
“…From 2014 to 2017, the faecal carriage of ESBL-producing E. coli and K. pneumoniae was determined in three different large cross-sectional studies in the Netherlands in the selections of predominantly healthy individuals in the population at large: the Livestock Farming and Neighbouring Residents' Health Study (VGO) [5], the ESBL-population study (ESBLAT) [6] and a study on ESBL-producing bacteria among vegetarians and non-vegetarians (Vega Study) [16]. The VGO study was performed from February 2012 to May 2014 among the general population aged 18–70 years old living in a livestock-dense area in the south of the Netherlands, and after consent to participate in further studies, ESBL-E/K faecal carriage was assessed between February 2014 and May 2015 [5].…”
Section: Text Short Reportmentioning
confidence: 99%
“…In the Vega Study, vegetarians and persons eating meat were actively contacted to submit faecal samples in order to study ESBL-E/K carriage between November 2015 and March 2017. More characteristics of the three studies are described in Table 1 and details of the respective studies and laboratory methods can be found in the cited references [5, 6, 16]. All individual level data of the three studies were combined into a new dataset in order to perform a pooled analysis.…”
Section: Text Short Reportmentioning
confidence: 99%